Lifestyle decreases risk factors for cardiovascular diseases - Slavíček, Jaroslav; Kittnar, Otomar; Fraser, Gary E; Medová, Eva; Konečná, Jana; Žižka, Robert; Dohnalová, Alena; Novák, Vladimír (Central European Journal of Public Health, 2008)
The morbidity and mortality of cardiovascular diseases is high in the developed countries. The lifestyle changes are capable to decrease it by 50%. The aim of the present study was to measure the parameters of some risk factors before and after a one-week NEW START rehabilitative retreat. 1349 volunteers, 320 men, 1029 woman, mean age 51 +/- 14.5 (SD) years participated in 30 rehabilitative retreats from 1999-2006 in the Czech Republic, using a low-fat, low-energy, lacto-ovo-vegetarian diet and exercise, in a stress-free environment. Body weight, height, BMI, blood pressure, heart rate, serum cholesterol and blood glucose were measured. Body weight decreased in 1223 measured persons from 71.2 +/- 14.38 (SD) to 70.6 +/- 14.02 kg (p<0.0001), BMI (1,046 measured persons) from 25.1 +/- 4.60 (SD) to 24.8+4.49 (SD) kg/m2 (p<0.0001), systolic blood pressure (1,218 persons) from 129.8 +/- 23.02 (SD) to 123.8 +/- 21.52 (SD) mmHg (p<0.0001), diastolic blood pressure (1210 persons) from 79.8 +/- 12.7 (SD) to 77.5 +/- 11.6 (SD) mmHg (p<0.0001), serum cholesterol (998 persons) from 4.86 +/- 0.95 (SD) to 4.32 +/- 0.77 (SD) mmol (p<0.0001), blood glucose (544 persons) from 4.31 +/- 1.59 (SD) to 3.88 +/- 1.33 (SD) mmol (p<0.0001). Heart rate was not significantly decreased. The parameters were lower in lacto-ovo vegetarians and Seventh-day Adventists than in controls who never observed the diet and avail the lifestyle programs. The parameters were nonsignificantly changed one year after finishing the retreat in the sample of 68 persons showing the positive effect of retreats. Our results showed, that the intake of a low-fat, low-energy diet, over the course of one week in a stress-free environment, had positive impact on the risk factors of cardiovascular diseases.
Keywords: Protestantism; Cholesterol; kardiovaskulární nemoci; Diet, Vegetarian; Humans; index tělesné hmotnosti; cholesterol; lidé středního věku; protestantismus; Body Mass Index; lázně; Female; rizikové faktory; Aged; dospělí; Heart Rate; senioři; lidé; Blood Glucose; dieta vegetariánská; kardiovaskulární rehabilitace; Health Resorts; Adult; Health Fairs; ženské pohlaví; Cardiovascular Diseases; krevní tlak; Life Style; srdeční frekvence; životní styl; Male; Middle Aged; krevní glukóza; Czech Republic; Body Weight; Exercise; tělesná hmotnost; mužské pohlaví; zdravotnické výstavy; cvičení; Česká republika; Blood Pressure; Cardiac Rehabilitation; Risk Factors